Crop coefficients of natural wetlands and riparian vegetation to compute ecosystem evapotranspiration and the water balance - Pereira, Luis S. (2024)
Wetlands, namely the riparian ones, play a major role in landscape and water resources functionalities and provide enormous opportunities for ecosystems services. However, their area at globe scale is continuously decreasing due to appropriation by the riverain communities or by allocation of water resources to other uses, namely irrigation, in prejudice of natural wetlands. Due to the high competition for water, namely for agricultural irrigation, the calculation of the vegetation evapotranspiration ( ETc), i.e. the consumptive water use of the wetland ecosystems, is mandatory for determining water supply–demand balance at various scales. Providing for the basin and local levels the reason for this review study on ETc to be presented in an irrigation focused Journal. The review also aims to make available adequate Kc values relative to these ecosystems in an ongoing update of FAO guidelines on evapotranspiration. The review on ETc of natural wetlands focused on its computation adopting the classical FAO method, thus the product of the FAO-PM grass reference ETo by the vegetation specific Kc, i.e., ETc = Kc ETo. This approach is not only the most common in agriculture but is also well used in natural wetlands studies, with Kc values fully related with vegetation ecosystems characteristics. A distinction was made between riparian and nonriparian wetland ecosystems due to differences between main types of water sources and main vegetation types. The Kc values are tabulated through grouping wetlands according to the climate since the variability of Kc with vegetation, soil, and water availability would require data not commonly available from the selected studies. Tabulated values appear to be coherent and appropriate to support field estimation of Kc and ETc for use in wetlands water balance when not measured but weather data may be available to compute the grass reference ETo. ETc and the water balance could then be estimated since they are definitely required to further characterization and monitoring of wetlands, defining measures for their protection, and assessing ecosystems’ services.